1981
DOI: 10.1192/bjp.139.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Change in Neurotic Depression: A Repertory Grid and Personal Construct Theory Approach

Abstract: Personal construct theory and repertory grid methodology were applied to a study of psychological change experienced by a sample of ten neurotic depressives and their matched controls during short-term hospitalization. All subjects completed a repertory grid and the Zung depression scale on admission to hospital. Depressives were characterized by lower self-esteem, more negative social perception and higher scores on the Zung scale. Both measures were repeated at the time of discharge from hospital. Depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…The negativity or positivity with which the person perceives the self can be assessed with the RepGrid by comparing ratings of the ''self'' with the ''ideal self,'' using Pearson correlations or distance scores (self-ideal). Previous RepGrid studies have found that persons with depressive disorders tend to have more negative self constructions than both normal and psychiatric samples (Ashworth, Blackburn, & McPherson, 1982;Axford & Jerrom, 1986;Hewstone, Hooper, & Miller, 1981;Sheehan, Fig. 1 Example of a RepGrid created by a specific participant in the Study 1981; Space & Cromwell, 1980;.…”
Section: Introductionmentioning
confidence: 97%
“…The negativity or positivity with which the person perceives the self can be assessed with the RepGrid by comparing ratings of the ''self'' with the ''ideal self,'' using Pearson correlations or distance scores (self-ideal). Previous RepGrid studies have found that persons with depressive disorders tend to have more negative self constructions than both normal and psychiatric samples (Ashworth, Blackburn, & McPherson, 1982;Axford & Jerrom, 1986;Hewstone, Hooper, & Miller, 1981;Sheehan, Fig. 1 Example of a RepGrid created by a specific participant in the Study 1981; Space & Cromwell, 1980;.…”
Section: Introductionmentioning
confidence: 97%
“…The lower the Euclidean distance between an entity and the child's real self, the greater the degree of identification with that entity and vice versa (Mackay, 1992). This and similar measures of identification (starting with Jones's study, 1961, on the Euclidean distance between elements) have been widely used (e.g., Adams-Webber, 1985b;Axford & Jerrom, 1986;Hewstone, Hooper, & Miller, 1981;Jones, 1961;Norris & Makhlouf-Norris, 1976;Sheenan, 1985;Slater, 1977) and are generally regarded as valid, stable, and reliable (Adams-Webber, 1979;Mackay, 1992;Sperlinger, 1976). Adams-Webber (1979) stated that the measure is "probably the most reliable of any structural index which can be derived from the repertory grids" (p. 40).…”
Section: Methodsmentioning
confidence: 96%
“…Además, cabría añadir que la diferencia encontrada en el número de elementos elicitados es menor en los sujetos depresivos, lo cual es indicativo de una menor red de relaciones interpersonales. Estos datos son coincidentes con investigaciones en las que se constata que lo que caracteriza a las personas con depresión es una autoestima significativamente menor y una percepción más negativa de sí mismos y de los demás (Axford y Jerrom, 1986;Hewstone, Hooper y Miller, 1981). En cuanto a la correlación «yo ideal» -«otros», los datos indican que los «otros» se acercan al «yo ideal», proporcionando un índice de buena adecuación percibida en los otros.…”
Section: Posición De Los Elementos «Yo Actual» Y «Yo Ideal»unclassified
“…El grupo de Feixas (Feixas y Cornejo, 1996;Feixas et al, 2008) establece una serie de perfiles tentativos en la construcción del sí mismo de acuerdo a estos tres índices, considerando el Perfil de Aislamiento en el caso de una correlación negativa entre «yo actual» -«yo ideal» y «yo actual» -«otros» y, una correlación positiva entre «yo ideal» -«otros». Este perfil, es característico de personas con depresión tal y como predice la teoría cognitiva de Beck (Beck, Rush, shaw y Emery, 1983) y que concuerda con los datos arrojados en otros estudios dentro del marco de la PCP (Axford y Jerrom, 1986;Feixas et al, 2008;Hewstone, Hooper y Miller, 1981;Oliver y McGee, 1982;space y Cromwell, 1980). …”
Section: Posición De Los Elementos «Yo Actual» Y «Yo Ideal»unclassified